Disentangling the signaling complexity of nerve growth factor receptors by CRISPR/Cas9. Issue 11 (3rd October 2022) - Testa, Giovanna; Mainardi, Marco; Vannini, Eleonora; Pancrazi, Laura; Cattaneo, Antonino; Costa, Mario
Abstract: The binding of nerve growth factor (NGF) to the tropomyosin–related kinase A (TrkA) and p75 NTR receptors activates a large variety of pathways regulating critical processes as diverse as proliferation, differentiation, membrane potential, synaptic plasticity, and pain. To ascertain the details of TrkA‐p75 NTR interaction and cooperation, a plethora of experiments, mostly based on receptor overexpression or downregulation, have been performed. Among the heterogeneous cellular systems used for studying NGF signaling, the PC12 pheochromocytoma‐derived cell line is a widely used model. By means of CRISPR/Cas9 genome editing, we created PC12 cells lacking TrkA, p75 NTR, or both. We found that TrkA‐null cells become unresponsive to NGF. Conversely, the absence of p75 NTR enhances the phosphorylation of TrkA and its effectors. Using a patch‐clamp, we demonstrated that the individual activation of TrkA and p75 NTR by NGF results in antagonizing effects on the membrane potential. These newly developed PC12 cell lines can be used to investigate the specific roles of TrkA and p75 NTR in a genetically defined cellular model, thus providing a useful platform for future studies and further gene editing.